Eksplorasi Corporate Guest Experience dalam Menilai Layanan Kamar dan Ruang Meeting di Whiz Prime Khatib Sulaiman Padang - Raysa Apriana Firdaus; Hendi Azwar (Lembaga Pengembangan Kinerja Dosen, 2024)
The study aims to explore the experience of corporate guests in evaluating room and meeting room services at the Whiz Prime Hotel Padang. The approach used in this research is qualitative research with an exploratory approach. Interviews, and documentation used for the data collection process. There are five informants from corporate guests who have already used the rooms and meeting rooms at the Whiz Prime Hotel Padang. By listening and transmitting and using Nvivo, QSR International software for qualitative data analysis. The results of this study show that the custumer experience dimension has a strong correlation with the corporate guest experience at the Whiz Prime Hotel Padang. As seen from the guest experience during your stay, the custumer experience dimension plays an important role for guests, staff and hotel Whiz Prime Hotel Padang. Companies can look at complaints as well as improve existing facilities to gain the experience of guests staying so that they can have a positive impact on the future of the hotel